A detailed review of the factors impacting pyramid type solar still performance - Karrar A. Hammoodi; Hayder A. Dhahad; Wissam H. Alawee; Z.M. Omara (Alexandria Engineering Journal, 2023)
Solar stills are commonly employed in solar desalination. On the other hand, solar still has low productivity. Many research projects are being carried out to improve the productivity of solar stills. This paper provides an overview of the detailed parameters affecting the performance of pyramid solar stills. These parameters are meteorological, design, and operating factors. The meteorological factors are solar irradiation, relative humidity, air speed, ambient temperature, and dust and cloud weather. In other respects, the operating parameters include the coloring of water, water flow, surfactant additives, salinity and contaminant levels, system maintenance water feeding, position of the solar still, and other effects. While the design Included are the number of basins and slopes, shapes of solar stills, inclination of the cover, thermal energy storage, basin absorption rates, reflectors and mirrors, sun tracking system, insulation thickness, additive materials, and water depth in the basin. From this perspective, in this review, we are attempting to research the current situation of various designs of pyramid solar stills. Based on many studies, the productivity of pyramid stills can be increased up to 35% with the use of PCM and up to 88% when using both v-corrugated absorber plates and PCM due to their increased heat storage capabilities. However, both reflectors and mirrors increase distillate productivity up to 48% and 53%, respectively. Furthermore, due to increased absorption of solar radiation, some types of nanoparticles increased solar productivity yield by up to 72%. Using this body of literature and other studies, it is concluded that climatic, design, and operating factors significantly influence the performance of the pyramid distiller. Furthermore, further work recommendations are proposed.